ORGANIZATION STRUCTURING MODEL DEVELOPMENT OF THE SURABAYA CITY GOVERNMENT - Diana Hertati (Universitas Sebelas Maret, 2016)
Structuring local government organizations system is important in the regional autonomy implementation, as it is one of the many instruments of decentralization principles. Structuring local organizations, as part of bureaucratic reform, aimed to create a government system that is efficient, effective and flexible. The flexibility in this case is based on the regional organization characteristics of the area, population and number of regional budget. In this regard, there is inconsistency in Surabaya City Government’s organization structuring, that is overly focused on the institutional issues, rigid standardization but does not consider other dimensions such as: human resources, system of governance, and the basic values of the organization. Based on this phenomenon a study is needed to formulate a model structuring for Surabaya City Government. To do so, researchers conducted a study in the following stages: (1) based on the criteria of the subject, the researchers chose one subject of the research; (2) based on the prior studies, researcher developed a research instrument consisting of local government assessment instruments - i.e. human resources, authorities, organization size, public service performance - in solving the Surabaya City Government’s structuring problem; (3) interviews were conducted based on the organization’s authorities; and (4) the data obtained is then described and analyzed using qualitative analysis method to obtain to develop a model for solving organizational structuring problem in Surabaya City Government. Keywords: Organisation Restructuring, Organisation Restructuring Model, Governance.